Efektivitas Penggunaan TikTok sebagai Media Pembelajaran Kosakata Bahasa Arab Siswa MAN 3 Ngawi - Qardhawi, Maulana Yusuf; Amrullah, Abdul; Kholil, Ahmad (Shaut al Arabiyyah, 2025)
This study aims to examine the effectiveness of using TikTok as a learning medium in Arabic vocabulary instruction, with a particular focus on improving students’ comprehension and learning motivation. The research employed a quasi-experimental design involving two class groups: an experimental group that used TikTok as a learning medium and a control group that applied conventional teaching methods. Data were collected through pretests and posttests to measure students’ mastery of Arabic vocabulary, along with classroom observations to assess their participation and engagement during the learning process. The results revealed that the experimental group experienced a significant improvement in Arabic vocabulary mastery, with an average posttest score of 80,89 higher than the control group’s average score of 39,94. Furthermore, students in the experimental group showed higher learning motivation and greater engagement. Despite some technical challenges such as limited internet access, overall, the use of TikTok proved to be an effective and engaging medium for teaching Arabic vocabulary at MAN 3 Ngawi.